An Analysis of Code Switching and Code Mixing in Fashion Program “I Look” on Net Tv - Renita Wati (Channing : Journal of English Language Education and Literature, 2020)
This study focuses on the form and function of code-switching and code-mixing used in the Fashion Program "I LOOK " on NET TV. This study is aimed to answer the following problem: 1.What is the forms of code-switching and code-mixing used in the Fashion Program "I LOOK" on NET TV, and What are the functions of code-switching and code-mixing in Fashion Program "I LOOK" on NET TV. To answer the problem, the writer used descriptive qualitative research through theoretical triangulation the total data 72 unit of analysis of code-switching found that 22 data used tag switching, 18 data used inter-sentential switching, and 32 used intra-sentential switching. It showed that intra-sentential switching is commonly used by Kimmy Jayanti in the fashion program "I LOOK" on NET TV. Furthermore, 127 unit data analysis of code-mixing performed 74 insertions of words, 48 insertions of phrases, 2 insertions of hybrids, and 3 insertions of reduplications. Meanwhile, there is 250 function of code-switching and code-mixing used by Kimmy Jayanti in the fashin program "I LOOK" in NET TV. They are quotation 1, addressee specification 24, repetition 1, interjection 31, message qualification 12, personalization and objectivization 15, and facility of expression 121.